2017
DOI: 10.1007/s10295-017-1944-x
|View full text |Cite
|
Sign up to set email alerts
|

A Bacillus subtilis strain as probiotic in poultry: selection based on in vitro functional properties and enzymatic potentialities

Abstract: We have proposed and validate an in vitro probiotic selection, based on enzymatic potentialities associated to well-established probiotic functional properties. A new Bacillus subtilis HB2 isolate, selected based on its high extracellular enzyme production, was chosen as a probiotic candidate for application as animal feed supplement. The HB2 strain showed an excellent acid and bile salts tolerance, a strong adhesion to chick enterocytes and produced antimicrobials against pathogens. An in vivo trial in poultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Other genera promoted in the birds with higher PU were Bacillus and Leuconostoc (Figure 1). Bacillus is considered as a probiotic in chickens; may improve bird performance [37]; exerts different enzymatic activities like amylase, xylanase, and pectinase [38]; and phosphatase activity can be expected from this genus, as previously reported in soils [39,40].…”
Section: Effect Of Pu Cau and Animal Performance On Microbial Distributionmentioning
confidence: 78%
“…Other genera promoted in the birds with higher PU were Bacillus and Leuconostoc (Figure 1). Bacillus is considered as a probiotic in chickens; may improve bird performance [37]; exerts different enzymatic activities like amylase, xylanase, and pectinase [38]; and phosphatase activity can be expected from this genus, as previously reported in soils [39,40].…”
Section: Effect Of Pu Cau and Animal Performance On Microbial Distributionmentioning
confidence: 78%
“…Such decrement might be due to action mode of bioactive additives inclusion which having a potential energy-sparing effect of ME containing diets as reported by Harrington et al (2015). Along the same line, Lee et al (2014) and Hmani et al (2017) reported that feed intake was statistically decreased with using B. subtilis in chicks diet compared with those unsupplemented. Also, Selim et al (2018) showed that enzymes supplementation (xylanase or Pectase or both of them) to broiler diets resulted in significant decrease in the amount of feed intake.…”
Section: Carcass Yieldmentioning
confidence: 62%
“…Moreover, coarse particles increased the relative abundance of Ruminoclostridium1 , Lachnospira and Ruminococcus1 , and numerically increased families like Lactobacillaceae and Bacillaceae, suggesting a greater relative abundance of butyric, propionic, and acetic producers [ 41 , 42 , 43 ]. Some of these bacteria are related to a better performance in broilers [ 44 , 45 ]. Thus, it seems that an improvement in the development of proximal GIT due to feeding coarser particle pelleted diets promoted positive changes in the intestinal microbiome, with significant increases in nutrient digestibility and VFA production.…”
Section: Discussionmentioning
confidence: 99%